Penerapan Media Komunikasi Dalam Pembelajaran Oleh Mahasiswa PPA Semester 3 - Nengsi Romawati Tarihoran; Raikhapoor Raikhapoor (Nubuat : Jurnal Pendidikan Agama Kristen dan Katolik, 2024)
This study aims to analyze the application of communication media in learning by third-semester students of the Advanced Education Program (PPA). Communication media plays a crucial role in the learning process as it can enhance understanding and interaction between lecturers and students. This research uses a descriptive approach with a survey method involving third-semester students from a university. The results of the study indicate that most students use various communication media, such as online learning platforms, instant messaging apps, and social media, to support their learning. These communication media have been proven effective in facilitating access to materials, group discussions, and communication between students and lecturers. However, challenges such as technological limitations and motivational issues were also identified. This study recommends that educational institutions continue to develop and utilize appropriate communication technologies to improve the quality of learning.